Penyuluhan Kefarmasian dan Pemeriksaan Kesehatan di Desa Gegelang, Lombok Barat - Mudawil Qulub; Indriani, Nurul; Qomaliyah, Eka Nurul; Ramandha, Muhammad Eka Putra; Kresnapati, I Nyoman Bagus Aji; Ramadhani, Muhammad Wisda Pradja (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The incidence of degenerative diseases is increasing every year. Degenerative diseases are caused by decreased organ function not only due to age but also due to lifestyle factors such as eating patterns, stress levels, and a history of other diseases. This community service is carried out in Gegelang Village, West Lombok, Indonesia. The aims of this community service are to detect degenerative diseases early and to provide an understanding of prevention to management as a preventive measure for several degenerative diseases. Methods used in these activities include providing free health checks, followed by health education training. Gegelang village received health education training on the causes and treatment of degenerative diseases specifically obesity, diabetes mellitus, hypertension, and uric acid. Health checks specifically that included measuring body mass index, checking blood pressure, blood sugar levels, and uric acid level. Of the 68 villagers who took part in the body mass index examination, the percentages of underweight, normal, overweight, and obesity types 1 and 2 were 5.89%, 23.53%, 22.06%, 29.41%, and 19.11%, respectively. Meanwhile, systolic blood pressure greater than 140 mmHg was 22.06%, and diastolic blood pressure greater than 90 mmHg was 11.27%. Examination of blood sugar during normal classification, high blood sugar levels at risk, and indications of diabetes in 58%, 23%, and 11%. The amount of uric acid included in the high classification is only 11%. Improving the quality of health, early detection, and management of degenerative diseases is urgently needed.